Development of Health Promotion with The Design of Heart Failure Patient Monitoring Instrument - Alfan Al Ghifari Sudarmanto; Mahendro Prasetyo Kusumo (Postgraduate, University of Mataram, 2023)
Heart disease, particularly heart failure, is a prevalent chronic condition requiring regular monitoring to maintain patients' well-being. This study aims to develop and validate a monitoring instrument for heart failure patients. A pilot study was conducted in two main stages: instrument development and pre-test post-test on a sample of outpatient heart failure patients at RSU Muhammadiyah Ponorogo from March to May 2023. The validity test revealed 17 valid questionnaire items, with Cronbach’s Alpha values for routine examination, physical activity, and nutrition domains being 0.729, 0.829, and 0.786, respectively, indicating good reliability. Sample testing demonstrated a significant improvement in patient compliance (p < 0.005) and nutritional status (p < 0.05) after cardiovascular health promotion. However, there was no significant change in physical activity. With a combination of high construct validity, good reliability, and strong content validity, the questionnaire proved to be a robust and reliable measurement tool. The findings depict significant changes in compliance and nutritional status among heart failure patients following health promotion interventions, emphasizing the need for further focus on physical activity aspects. These results can contribute to the development of more effective monitoring and care strategies for heart failure patients.